1979
DOI: 10.1073/pnas.76.11.5694
|View full text |Cite
|
Sign up to set email alerts
|

Cellular localization of the insect prothoracicotropic hormone: In vitro assay of a single neurosecretory cell

Abstract: The distribution of prothoracicotropic hormone in the pupal brain of Manduca sexta has been determined by an in vitro assay for prothoracic gland activation. Prothoracicotropic activity was observed in both the brain and retrocerebral complex, but predominantly in the dorsolateral regions of the protocerebrum. Of the two groups of neurosecretory cells present in this area of the brain, only the two lateral type III neurosecretory cells exhibited significant prothoracicotopic hormone activity. Further analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
48
0

Year Published

1984
1984
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(49 citation statements)
references
References 15 publications
1
48
0
Order By: Relevance
“…A large number of hormonal factors in addition to EH have been attributed to the cerebral neurosecretory systems of insects (reviewed in Downer and Iaufer, 1983;Raabe, 1982), but in only one previous instance-the localization of prothoracicotropic hormone to the Group III cell clusters of pupal Manduca (Agui et al, 1979)-has the function of an identified set of brain neurosecretory cells been unambiguously confirmed. Similarly, the physiological changes accompanying the release of many of these factors have been examined, primarily with extracellular recording (Copenhaver and Truman, 1984;Orchard and Steel, 1980;Ruegg et al, 1982) and stimulating techniques (Girardie and Girardie, 1977;Orchard et al, 1981;Scharrer and Rater, 1969).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A large number of hormonal factors in addition to EH have been attributed to the cerebral neurosecretory systems of insects (reviewed in Downer and Iaufer, 1983;Raabe, 1982), but in only one previous instance-the localization of prothoracicotropic hormone to the Group III cell clusters of pupal Manduca (Agui et al, 1979)-has the function of an identified set of brain neurosecretory cells been unambiguously confirmed. Similarly, the physiological changes accompanying the release of many of these factors have been examined, primarily with extracellular recording (Copenhaver and Truman, 1984;Orchard and Steel, 1980;Ruegg et al, 1982) and stimulating techniques (Girardie and Girardie, 1977;Orchard et al, 1981;Scharrer and Rater, 1969).…”
Section: Discussionmentioning
confidence: 99%
“…The relative simplicity of the arthropod CNS has made possible the unambiguous identification of peptidergic cells and cell groups (Bullock, 1984;Rowell, 1976), and direct analysis of the contents of individual neurosecretory somata has revealed the cellular localization of peptides that modulate steroid secretion (Agui et al, 1979), diuresis (Berlind and Maddrell, 1979), skeletal muscle contraction (O'Shea and , heartbeat acceleration (O'Shea and Adams, 198 1; Tublitz and Truman, 1985), and stage-specific cuticular tanning (Taghert and Truman, 1982). The electrophysiological properties of individual neurosecretory cells have also been determined in several different preparations (Bruce and Wilkens, 1976;Carrow et al, 1984;Miyazaki, 1980;Zaretsky and Loher, 1983), although attempts to monitor the spontaneous activity of peptidergic neurons in a physiologically relevant context have proven less successful.…”
mentioning
confidence: 99%
“…The brain of the silkworm, Bombyx mori, produces prothoracicotropic hormone (PTTH), the primary stimulator of temporal transition, in two pairs of lateral neurosecretory cells (LNCs) (Agui et al, 1979;Kawakami et al, 1990;Mizoguchi et al, 1990). PTTH signals the prothoracic glands (PGs) to trigger production and release of ecdysone, the precursor of its active metabolite 20-hydroxyecdysone (20E) (Kawakami et al, 1990;Gilbert et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to other neurohormones, allatostatins are synthesized in the dorsolateral neurosecretory neurons (NSN) of the insect protocerebrum (Veelaert et al, 1995), along with the large form of the prothoracicotropic neuro hormone (PTTH) (Agui et al, 1979;Dai et al, 1994).…”
Section: Introductionmentioning
confidence: 99%